Experimental Study and Numerical Analysis on the Vibration Characteristics of a Terraced Slope along an Embankment Section of a High-Speed Railway - Wujian Yan; Haizhong Zheng; Zhijian Wu; Tong Wan; Xinxin Tian (Shock and Vibration)
The characteristics of the vibrations induced by the passage of a high-speed train do not only depend on the train speed, axle load, and track irregularity but also depend on the properties of the foundation soil and the surrounding topography. Estimating the vibration characteristics in different terrains is therefore essential. This study investigates the characteristics of propagation and attenuation of the vibrations induced by high-speed trains in loess-terraced slopes. The influence of the soil mechanical properties on the propagation of vibrations is analyzed through a numerical simulation. Field experiments are conducted to measure the vibration induced by a high-speed train at a loess-terraced slope site in Qin’an, Gansu, China. The measured acceleration time history is analyzed in the time domain and frequency domain. The results show that, at the edge of each terrace level, the vibration in the Y direction is the strongest, followed by those in the X and Z directions. The peak ground acceleration values are amplified in all three directions at the fourth terrace level. A model describing the vehicle-roadbed-foundation-terraced slope system is established to study the influence of the elastic modulus of the soil on the vibration characteristics. A change in the elastic modulus of the foundation soil is found to have an evident influence on the horizontal and vertical vibrations in each terrace level. However, a change in the elastic modulus of the soil in a terrace only affects the vibration in that terrace and in the adjacent ones, whereas it has no effect on the vibrations in terraces located farther away. This study can provide some reference values for slope reinforcement along railways.